HERBAL TWINNING SYSTEM (HERBAL TREATMENT WITH MONITORING ANALYSIS SYSTEM): RANCANG BANGUN APLIKASI KONSELING PENYAKIT DEGENERATIF DALAM KAIDAH IPE BERBASIS ANDROID - Diana Gusti Ambarwati; Wahyu Nur Hidayati; Khairunnisa Aisyanti; Heru Supriyono (Jurnal Ilmiah SINUS, 2018)
The cause of death in the world's largest is non-communicable diseases or degenerative diseases. According to WHO (2013), 63% kill 36 million people per year, 80% of these deaths occur in middle and low income countries. From the economic point of view, the danger of this disease is very burdensome to the community because it requires high cost for hospitalization. Herbal Twinning System (Herbal Treatment with Monitoring Analysis System) is an android-based renewable application that is used to facilitate the sufferers of degenerative diseases to get an information about the proper and rational treatment. Health professions in the form of doctors, pharmacists, nurses, and nutritionists act as facilitators to facilitate patients in consultation related to the illness. This application has five main menu that is to health, to consultation, to herbal, to nutrition, and to discussion which contains information related to processing of simple herbal medicine that can be used as a substitute for chemical drugs, tips on healthy lifestyle, and control of patient nutrition. Application design created using android studio, XAMPP SQL, and. notepad, The results of the application include the design of systems that can be applied in mobile phones or tablets.